Comparison between Health Care Management Students Instructors Point of View about Internship lessons in this major Isfahan University of Medical Sciences 2006 - Marzieh Javadi; Ahmad Reza Raeisi; Marzieh Golkar (Kerman University of Medical Sciences, 2008)
Background & Objective: Internship is an important and basic element in each field especially health care management A great deal of students knowledge is put into practice during this period Evaluation of internship status is necessary for improving its quality This study was performed to evaluate the health care management internship status in several aspects based on students and teachers point of view Methods: In this descriptiveanalytic study 102 health care management teachers and students from Isfahan University participated The data was collected using a researcher made questionnaire in which the general internship lessons status learning process learners teachers internship fields were included Results : The mean given scores after evaluation by teachers and students were 3936 (considered as good) and 2806 (considered as moderate) respectively The result of analysis showed that the weakest aspect of internship according to the students point of view was internship fields (hospital and health care centers) with a mean score of 226 and the weakest point according to the teachers point of view was about the learners (334) Teachers believed that the biggest problem was due to the transportation system ( =25) whereas students believed it to be due to lack of information by health care personnel about educational needs ( =1843) Conclusion : Internship lessons esp in internship fields which were given the least score by attendants need more attention In order to improve the situation of internship it is recommended to provide more facilities during internship period and focus on familiarizing briefing and attracting health care personnel